2004
DOI: 10.1214/ecp.v9-1116
|View full text |Cite
|
Sign up to set email alerts
|

Ergodicity of PCA: Equivalence between Spatial and Temporal Mixing Conditions

Abstract: For a general attractive Probabilistic Cellular Automata on S Z d , we prove that the (time-) convergence towards equilibrium of this Markovian parallel dynamics, exponentially fast in the uniform norm, is equivalent to a condition (A). This condition means the exponential decay of the influence from the boundary for the invariant measures of the system restricted to finite boxes. For a class of reversible PCA dynamics on {−1, +1} Z d , with a naturally associated Gibbsian potential ϕ, we prove that a (spatial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The spatial mixing of the invariant measure is known for certain classes of ergodic PCA (see e.g. [39,55,45,43,10,6], as well as [59,47,31] in which the unique invariant measure is explicitly known). However, even the weaker condition of spatial ergodicity (≡ ergodicity under the shift action) is not known for general ergodic PCA.…”
Section: Ergodicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial mixing of the invariant measure is known for certain classes of ergodic PCA (see e.g. [39,55,45,43,10,6], as well as [59,47,31] in which the unique invariant measure is explicitly known). However, even the weaker condition of spatial ergodicity (≡ ergodicity under the shift action) is not known for general ergodic PCA.…”
Section: Ergodicitymentioning
confidence: 99%
“…For the class of PCA that are monotonic with respect to a total ordering of the alphabet, Louis [43] has provided a necessary and sufficient condition for exponential ergodicity in terms of a spatial mixing condition. Proposition 2.2 above established the computability of the unique invariant measure for every ergodic PCA.…”
Section: Problem 1 Is Every Ergodic Pca Uniformly Ergodic?mentioning
confidence: 99%
“…Later, [23] showed that for translation-invariant attractive systems, the WSM condition (1.2) is in fact equivalent to (1.1). From our point of view, the main advantage of the WSM condition (1.2) is that we can show it to hold true throughout the uniqueness regime for ferromagnetic interactions.…”
Section: Previous Resultsmentioning
confidence: 99%
“…It was also used in Maes (1993). Recently, the coupling constructed in this paper was used to state some necessary and sufficient condition for the exponential ergodicity of attractive PCA's (see Louis (2004)). This last result relies on the fact that our coupling preserves a stochastic order between the configurations (so called increasing coupling).…”
Section: Introductionmentioning
confidence: 99%
“…We also give several examples and general applications of the constructed coupling. Indeed, the motivation for coupling together three or more PCA's comes from the paper Louis (2004), where a comparison between four different PCA dynamics proved to be useful.…”
Section: Introductionmentioning
confidence: 99%